The pleotropic role of statins: Could it be the imminent host modulation agent in periodontics? - Harpreet Singh Grover; Shailly Luthra; Shruti Maroo; Niteeka Maroo (Dental Research Journal, 2013)
Periodontal disease is a chronic inflammatory disease which represents a primarily anaerobic Gram-negative oral infection that results in gingival inflammation, loss of attachment, bone destruction. Bacterial endotoxins in the form of lipopolysaccharides (LPS) that are instrumental in generating a host-mediated tissue destructive immune response by mobilizing their defensive cells and releasing cytokines like Interleukin-1β (IL-1β), Tumor Necrosis Factor-α (TNF-α), and Interleukin-6 (IL-6), which lead to tissue destruction by stimulating the production of the collagenolytic enzymes: Matrix metalloproteinases (MMPs). Since the host-mediated tissue destruction is to be controlled, various means have been employed for modulating this response. Statins, 3-hydroxy-3-methylglutarylcoenzyme A (HMG CoA) reductase inhibitors, besides having lipid-lowering abilities also have antioxidant, antithrombotic, anti-inflammatory, immunomodulatory and osteomodulatory properties . All of these pleiotropic effects of statins point out to it perhaps becoming the novel host modulation agent in periodontics.